2010
DOI: 10.1292/jvms.09-0576
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella Isolated from the Feces of Migrating Cranes at the Izumi Plain (2002-2008): Serotype, Antibiotic Sensitivity and PFGE Type

Abstract: ABSTRACT. From November 2002 to February 2008, 2,251 crane feces were collected at the Izumi Plain in Kagoshima Prefecture. Salmonella enterica was isolated from 359 feces (15.9%), of which 332 (92.5%) were Salmonella Typhimurium (ST), 9 were S. Hvittingfoss/II, 4 were S. Abaetetuba, 3 were S. Enteritidis, 2 were S. Konstanz, 1 was S. Pakistan and 8 were untyped isolates, respectively. Against 12 antimicrobial agents, no resistant strains were found in 154 isolates examined, but one was found to be resistant t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 5 publications
0
11
1
Order By: Relevance
“…Salmonella estimated prevalence in our study was greater compared to that in Afro-Palearctic migrants captured at Ottenby bird observatory during fall migration from continental Europe to West Africa (Hernandez et al 2003 ) or birds in Greater Chicago (Hamer et al 2012 ). In contrast, our prevalence is lower than reports of 15.9% (6.4–43.5%) fecal shedding in migrating cranes at Izumi plain in Japan (Kitadai et al 2010 ). A possible explanation is that prevalence is influenced by feeding ecology.…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…Salmonella estimated prevalence in our study was greater compared to that in Afro-Palearctic migrants captured at Ottenby bird observatory during fall migration from continental Europe to West Africa (Hernandez et al 2003 ) or birds in Greater Chicago (Hamer et al 2012 ). In contrast, our prevalence is lower than reports of 15.9% (6.4–43.5%) fecal shedding in migrating cranes at Izumi plain in Japan (Kitadai et al 2010 ). A possible explanation is that prevalence is influenced by feeding ecology.…”
Section: Discussioncontrasting
confidence: 93%
“…This study detected 18 different serovars across study sites and found a diverse array of bird associated serovars ( n = 12) compared to previous studies that mainly found S. Typhimurium (Hughes et al 2008 ; Kitadai et al 2010 ). While prevalence in birds across sampling sites was not significantly different, the serovar distributions were different, and no serovars were shared between all sampling sites.…”
Section: Discussionmentioning
confidence: 52%
“…On the other hand, the presence of C. jejuni in our study and the implication of sandhill cranes as the source of a C. jejuni food-borne outbreak suggest that these migratory birds may carry human-pathogenic bacteria for long distances (8). Besides Campylobacter, pathogenic species of Salmonella and Mycobacterium have been isolated from cranes (17,34). Altogether, cranes seem to be a reservoir of many bacterial pathogens and potentially contribute a significant level of human health risk.…”
Section: Resultsmentioning
confidence: 61%
“…Wild birds may act as reservoirs of antimicrobial-resistant bacteria [9]. Of 156 Salmonella isolates recovered from crane fecal samples collected in the Izumi plain during the period between 2002 and 2008, however, all the isolates except for one each isolate were susceptible to ABPC and GM [8,12]. The resistance genes detected in the present study might not be easily transferred to Salmonella.…”
mentioning
confidence: 59%